Analisis Kadar Alkohol Pada Minuman Khas Sinjai Berdasarkan Penambahan Susu Dan Tanpa Susu - Rudy Hartono; Yaumil Fachni Tandjungbulu; Alfin Resya Virgiawan; Rahman Rahman; Zulfian Armah; Kirani B (Direktorat Politeknik Kesehatan Makassar, 2024)
Typical Sinjai Drink (MINAS) is made from fermented cassava, which contains alcohol of the ethanol type. Excessive alcohol consumption can lead to health problems, even death. Milk has protein and fat content that can reduce alcohol levels. This study aims to see the results of the examination of alcohol levels in MINAS based on the addition of milk and without milk. This type of research is an analytical observational with a cross section approach, the number of samples obtained in this study were 16 samples, namely 8 samples from seller A and 8 samples from seller B, each of the 8 seller samples included 4 samples with added milk and 4 samples without added milk that met the inclusion criteria in this study. The place of sample collection was carried out in Lappa Village, Sinjai Regency and sample examination was carried out at the Makassar Health Laboratory Center, South Sulawesi on 04-09 May 2023. The results showed that the average alcohol content of MINAS seller A without milk (1.6%) and milk addition (1.5%). The average alcohol content of MINAS seller B without milk (1.9%) and milk addition (1.7%). So it can be concluded that the alcohol content of MINAS with added milk is lower than MINAS without added milk, and it can be suggested for further researchers to pay attention to other factors that can affect the results of alcohol content examination. Keywords: Typical Sinjai Drink, Alcohol Content, Milk